Lilith and Peter Pan: A Comparison - Homolková, Barbora (Univerzita Pardubice, 2012)
The thesis deals with two books written by the Scottish authors George Mac Donald and J. M. Barrie. The books are Lilith and Peter Pan. The aim of the thesis is to compare the main characters from the point of view of several specific features.
Lilith and Petr Pan: Porovnání
Keywords: Lilith; Petr Pan; Mac Donald, George; Barrie, J. M.; fantazy žánr; Lilith; Peter Pan; fantasy genre